'Two way' shape memory composites based on electroactive polymer and thermoplastic membrane. (November 2016) - Yao, Yongtao; Zhou, Tianyang; Wang, Jingjie; Li, Zhenghong; Lu, Haibao; Liu, Yanju; Leng, Jinsong
Abstract: A practical and facile strategy was proposed to fabricate composites that not only use the properties of individual components (commercial electroactive polymer and thermoplastic resin) to their advantage, but also produce synergy effect of 'two way' shape memory properties. In this design, electroactive polymer is treated as soft segment which provides actuation force via converting electrical energy to dynamic energy. Thermoplastic material serves as 'hard segment' to help with fixation of temporary shape thanks to its re-structuring and stiffness/modulus changing abilities through the reversible transitional temperature. Compared with traditional one way and two way shape memory materials, this composite material has the capability of changing shape without pre-programming. High shape recover property (99 ± 0.3%.) has been obtained due to the rubber elasticity of electroactive polymer matrix. Many features could be brought up based on this design, such as accurate control over deformation by changing strength of applied electric field as well as tailorable stimulus temperature and mechanical properties.